PERAN KEPALA DESA DALAM MENINGKATKAN KEPEDULIAN MASYARAKAT TERHADAP KEAMANAN LINGKUNGAN DI KAMPUNG PASIR MUNCANGDESA PANOSOGAN KECAMATAN CIKEUSAL KABUPATEN SERANG - Siti Nurjanah; Anton Aulawi; E. Nita Prianti (Bajang Institute, 2022)
This research was conducted in Pasir Muncang Village, Panosogan Village, Cikeusal District, with the aim of 1) knowing 1. To find out the role of the Village Head in increasing public awareness of environmental security in Pasir Muncang Village, Panosogan Village, Cikeusal District, Serang Regency. 2. To find out the efforts of the Head of Panosogan Village, Cikeusal District, Serang Regency on environmental security conditions. The method in this study used a qualitative descriptive method. The analysis used is by using triangulation with data reduction techniques, data display and data verification. The results obtained in this study are that the role of the village head is good, namely contributing 64% regarding environmental security for its citizens